Energy and cooling performance of carbon-dioxide and hydrofluoroolefins blends as eco-friendly substitutes for R410A in air-conditioning systems - Bukola Olalekan Bolaji; Deborah Olufunke Bolaji; Semiu Taiwo Amosun (Universitas Muhammadiyah Magelang, 2023)
Air-conditioning and refrigeration systems are electrical appliances that use a huge amount of energy and contribute indirectly to global warming. Also, R410A which was initially developed as a substitute for ozone-depleting refrigerants in the air-conditioning systems has been phase-out due to its high global warming potential (GWP) and the resulting harmful effect on the climate. In addition to the issue of refrigerant high GWP, energy consumption is a significant issue. The energy efficiency of new refrigerants must then be considered in the search for alternative refrigerants to ensure that they do not lead to an increase in greenhouse gas generation at the power source. Therefore, this paper investigates the energy and cooling performance of four new multi-components and ecologically friendly refrigerant blends that contained carbon dioxide and hydrofluoroolefins in their compositions as substitutes for R410A in air-conditioning systems. Relevant thermodynamic equations and REFPROP software were employed for the computational analysis. The results indicated that the new blends (R445A, R455A, R470B and R470A) exhibited a desirable low compression ratio and high heat transfer for cooling applications. The blends also exhibited low compressor energy input and low specific cooling energy. R455A has an average coefficient of performance (COP) of 24.6% above that of the reference refrigerant (R410A). The cooling capacity per unit volume for R470B, R455A and R470A across a temperature range of 253 to 293 K are higher by 1.3, 6.0, and 12.6%, respectively than that of R410A. Generally, among all the four new substitute blends, the overall assessment revealed R455A as the best replacement for R410A in air-conditioning systems due to its superior performance in terms of its low compression ratio, compressor energy and specific cooling energy. R455A also has the highest COP and relatively high cooling capacity per unit volume.